Stakeholder Analysis for Farmer inclusive Value chain Development in Mango - K, Nadhika; Krishnankutty, Jayasree (Journal of Extension Education, 2017)
Mango is being cultivated over a substantial area in Palakkad District of Kerala state. Being one of the significant agricultural commodity value chains existing in Kerala, the mango value chain of Palakkad district needs urgent attention to improve its performance. The study highlights the stakeholder analysis and SWOC matrix analysis of the mango sector. Stakeholders were asked to identify the strengths, weaknesses, opportunities and challenges in the mango sector. Based on the highest score obtained, four strategic options viz., enhancing value addition and product development, promotion of branding, educating the farmers on building competitiveness and increasing export potential by addressing quality parameters were identified.